The efficacy of large-scale affirmative action at elite universities - Cecilia Machado; Germán Reyes; Evan Riehl (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2023)
We study the effects of affirmative action at an elite Brazilian university that adopted race- and income-based quotas for 45 percent of its admission slots. We link admission records to national employer-employee data to examine how the policy affected the careers of both its targeted beneficiaries and the university's other students. For students admitted through affirmative action, the policy led to a modest increase in early-career earnings that faded as their careers progressed. Conversely, the adoption of affirmative action caused a large and persistent decrease in earnings for the university's most highly ranked students. We present evidence that these negative earnings effects are driven by a reduction in human capital accumulation and a decline in the value of networking.
Keywords: I26; J24; J31; 330